2024
DOI: 10.1051/e3sconf/202448802005
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Heat Transfer Analysis of Evacuated Tube Solar Collector Using MXene/Soyabean Oil Nanofluid

Nur Amirah Awis,
Syed Awais Ali,
Mumtahina Mim
et al.

Abstract: This study focuses on investigating the thermo-hydraulic performance and entropy generation rate of an evacuated tube solar collector using MXene/Soybean oil as a working nanofluid by means of Computational Fluid Dynamics (CFD). A complete 3-D geometry is considered using three different kinds of working fluids (water, soybean oil and MXene/Soybean oil-0.025 wt.%, 0.075 wt.%, and 0.125 wt.%) for five different mass flow rates (0.02475 kg/s, 0.04818 kg/s, 0.0717 kg/s, 0.0952 kg/s, and 0.1188 kg/s) under same so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Similarly, Sreekumar et al 287 reported the performance of MXene/C.dot to enhance the thermohydraulic performance of a PV/T system, with an enhancement in thermal efficiency to 57.45%, which is 9.45% improved over DI-water. Awis et al 288 reported the sky-high thermohydraulic performance of MXene/SO in achieving a thermal efficiency of 31% with a low entropy generation rate when compared to water. Another hybrid PV/T module was designed by Das et al 289 with a binary solution of MXene dispersed in an ionic liquid.…”
Section: Mxene-based Energy Management Systemsmentioning
confidence: 99%
“…Similarly, Sreekumar et al 287 reported the performance of MXene/C.dot to enhance the thermohydraulic performance of a PV/T system, with an enhancement in thermal efficiency to 57.45%, which is 9.45% improved over DI-water. Awis et al 288 reported the sky-high thermohydraulic performance of MXene/SO in achieving a thermal efficiency of 31% with a low entropy generation rate when compared to water. Another hybrid PV/T module was designed by Das et al 289 with a binary solution of MXene dispersed in an ionic liquid.…”
Section: Mxene-based Energy Management Systemsmentioning
confidence: 99%